Evaluations of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios for abdominal aortic calcification in peritoneal dialysis patients - Xing Wen-xiu; Ren Cai-xia; Lu En-bang; Gong Xue; Liu Yuan; Wan Mei-yan (Linchuang shenzangbing zazhi)
Objective To explore the value of neutrophil-to-lymphocyte ratio（NLR）and platelet-to-lymphocyte ratio（PLR）in the evaluation of abdominal aortic calcification（AAC）in peritoneal dialysis（PD）patients.Methods From 2018 to 2019,a total of 72 patients with chronic kidney disease（CKD）in stage 5 undergoing regular PD at Qingdao Municipal Hospital were recruited.Their general and clinical biochemical parameters were collected and the values of NLR/PLR calculated.Based upon AAC scores,they were divided into non/mild calcification group（0≤AACs≤4）and moderate-severe group（AACs>4）.For elucidating the correlation between AAC,NLR and PLR,clinical parameters and diagnostic values of NLR/PLR for moderate-severe AAC were examined.Results The proportion of calcification was 83.3% and the proportion of moderate-severe calcification 52.8%.Significant inter-group differences existed in age,dialytic age,counts of neutrophil/platelet/lymphocyte,NLR,PLR,albumin,corrected calcium,calcium-phosphorus product,alkaline phosphatase,C-reactive protein（CRP）and triglyceride（TG）（P<0.05）.AAC was positively correlated with age,dialytic age,neutrophils,platelets,NLR,PLR,blood phosphorus,corrected calcium,calcium-phosphorus product,alkaline phosphatase,CRP,TG（P<0.05）and negatively correlated with albumin and lymphocyte count（P<0.05）.NLR was positively correlated with age,neutrophil count,alkaline phosphatase,CRP and AACS（P<0.05）while negatively correlated with lymphocyte count and albumin（P<0.05）.PLR was positively correlated with age,neutrophil count,platelet count,CRP and AACs（P<0.05）while negatively correlated with lymphocyte count and albumin（P<0.05）.The area under ROC curve of NLR/PLR for moderate/severe abdominal aortic calcification was 0.844（cutoff point 3.88,sensitivity 0.868,specificity 0.706）and PLR curve 0.784（cutoff point 193.03,sensitivity 0.763,specificity 0.735）.Conclusions Both NLR and PLR are correlated with AAC and inflammation in PD patients.Yet NLR has a better diagnostic value for AAC in PD patients.